Occupational disorders in dental practice: an integrative review of risk factors - Silva, Bruna De Oliveira; Martins, Ronald Jefferson; Saliba, Nemre Adas; Moimaz, Suzely Adas Saliba; Saliba, Tânia Adas (Revista Cubana de Salud y Trabajo, 2025)
Introduction: Occupational diseases represent significant challenges for professionals, affecting quality of life and productivity. Among these diseases, work-related musculoskeletal disorders and repetitive strain injuries stand out, especially common among dental surgeons due to inadecuate postures. Objectives: To determine the prevalence of musculoskeletal diseases in dental surgeons, as well as to identify the main factors influencing this occurrence. Methods: This integrative review, conducted between June and October 2023, analyzed articles from the past ten years in the databases PubMed, Scopus, Biblioteca Brasileira de Odontologia, and Web of Science, using specific descriptors. Eligibility criteria included observational studies with a minimum sample size of 50 participants, published in peer-reviewed journals in Portuguese or English. Data analysis and collection were conducted independently by two researchers, following a standardized protocol for data extraction in integrative reviews (URSI, 2005). Results: Recent studies highlight the high incidence of musculoskeletal pain among these professionals, emphasizing the need for ergonomic interventions and preventive practices starting from academic training. Conclusion: The relationship between musculoskeletal disorders and quality of life indicates specific risks for dental surgeons, justifying the implementation of preventive approaches